The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/mec.14036
|View full text |Cite
|
Sign up to set email alerts
|

A combination of sexual and ecological divergence contributes to rearrangement spread during initial stages of speciation

Abstract: Chromosomal rearrangements between sympatric species often contain multiple loci contributing to assortative mating, local adaptation and hybrid sterility. When and how these associations arise during the process of speciation remains a subject of debate. Here, we address the relative roles of local adaptation and assortative mating on the dynamics of rearrangement evolution by studying how a rearrangement covaries with sexual and ecological trait divergence within a species. Previously, a chromosomal rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 112 publications
2
64
0
Order By: Relevance
“…It is tempting to speculate that RI in the gall former-live oak system is a product of adaption to divergent host plant environments and thus has a genetic basis. A number of studies of plant-insect systems, including Rhagoletis pomonella fruit flies and European corn borer, have revealed that allochrony during population divergence is linked to differences in the timing of diapause life history, is genetically controlled, and highly polygenic Kozak et al 2017;Ragland et al 2017;Doellman et al 2018). However, temporal RI also may represent plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that RI in the gall former-live oak system is a product of adaption to divergent host plant environments and thus has a genetic basis. A number of studies of plant-insect systems, including Rhagoletis pomonella fruit flies and European corn borer, have revealed that allochrony during population divergence is linked to differences in the timing of diapause life history, is genetically controlled, and highly polygenic Kozak et al 2017;Ragland et al 2017;Doellman et al 2018). However, temporal RI also may represent plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…In many diverging populations of Lepidoptera, ecological factors such as host plant use co‐vary with differences in sexual signals (Groot et al, ; Joyce et al, ), but in few cases has the relative contribution of these factors to genetic structure been tested (Gouin et al, ; Prowell, McMichael, & Silvain, ). Ostrinia nubilalis is an emerging model for speciation dynamics due to sympatric ecotypes or strains that vary in voltinism and sex‐pheromone communication (Coates et al, ; Dopman et al, ; Kozak et al, ; Lassance, ; Olsson et al, ). Ecological differences in host plant preference occur between closely related O. nubilalis strains in North America (O'Rourke et al, ) and among Ostrinia species in Europe (Bethenod et al, ; Bourguet, Bethenod, Trouve, & Viard, ; Bourguet et al, ; Frolov et al, ; PĂ©lozuelo, Malosse, Genestier, Guenego, & FrĂ©rot, ; PĂ©lozuelo et al, ; Thomas, Bethenod, Pelozuelo, FrĂ©rot, & Bourguet, ).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of the European corn borer, Ostrinia nubilalis (HĂŒbner) (Lepidoptera: Crambidae), vary in ecological and sexual traits, and this species has emerged as a model for studying mechanisms of ecological diversification and the formation of incipient species (Coates, Dopman, Wanner, & Sappington, ; Dopman, ; Kozak et al, ; Lassance, ; Wang et al, ). Ostrinia nubilalis is a polyphagous lepidopteran native to Europe and western Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work found sex-linked inheritance (31, 32) and 67 evidence for a single quantitative trait locus (QTL) on the Z (sex) chromosome (25). However, a putative 68 inversion encompassing 39% of the Z chromosome was discovered and the QTL was locked into a non-69 recombining region along with hundreds of genes, many of which were differentially expressed during 70 diapause break (33)(34)(35). Subsequent work demonstrated that the recombination suppressor is polymorphic 71 in field populations (35) and we therefore performed QTL mapping in pedigrees with putatively collinear Z 72 chromosomes.…”
mentioning
confidence: 99%
“…However, a putative 68 inversion encompassing 39% of the Z chromosome was discovered and the QTL was locked into a non-69 recombining region along with hundreds of genes, many of which were differentially expressed during 70 diapause break (33)(34)(35). Subsequent work demonstrated that the recombination suppressor is polymorphic 71 in field populations (35) and we therefore performed QTL mapping in pedigrees with putatively collinear Z 72 chromosomes. An advantage of this approach is that it will exclusively identify the genetic architecture of 73 diapause timing, but a challenge is that individual genes or mutations associated with trait differences 74 cannot be easily identified.…”
mentioning
confidence: 99%